ESTIMATION OF ENTRANCE SURFACE DOSE TO ADULT PATIENTS UNDERGOING PLAIN CHEST RADIOGRAPHIC EXAMINATIONS IN A NORTHERN NIGERIAN POPULATION - Njiti MM; Nwobi IC; Garba I; Ahidjo A; Bashir T; Abubakar A; Hamidu AU; Luntsi G (Ntec Specialist, 2014)
Objective: The entrance surface doses (ESD) to adult patients undergoing posteroanterior (PA) chest radiography were measured at Shika Ahmedu Bello University Teaching Hospital (ABUTH) Zaria, Northern Nigeria. Method: A total of 30 patients were prospectively considered in the study. The ESDs were obtained using thermo luminescence dosimeter (TLDs) chips, and Kumar's formula. Results: The estimated ESD obtained were 1.08 mGy and 0.76 mGy for TLD chips readings and Kumar's formula respectively. Comparison was made between the two readings, and a statistically significant difference was noted (p less than 0.029). Conclusion: Procedural changes are suggested in order to lower the ESD and enhance the image quality of the radiographs. ESDs in this study were found to be generally higher compared with those reported in similar studies in Southern Nigeria, UK, and CEC. The results call for improved operators technique and application of quality Assurance Programme (QAP) in radiology departments to ensure that doses are kept as low as reasonably achievable, and also for the formulation of local diagnostic reference levels (LDRL)